THE INFLUENCE OF THE TEMPERATURE REGIME ON THE PRODUCTIVITY OF THE SILKWORM (Academia Science Repository, 2023)
The article gives information about the influence of one of many external factors on the growth and development of silkworm caterpillars, the temperature conditions, its influence in the stages of eggs, pupa, butterflies, in what temperature conditions they should be contained, especially in the tracked period when they feed, develop and determine the fate of the future harvest cocoons, the duration of each age and the tracked period in general, how to maintain the optimal temperature regime, how they are measured, and how and what measures are taken when the temperature rises and falls from the optimal temperature